Achieving Sustainable Development Goals through Traditional Knowledge Systems and Millet Cultivation - Kumar, Mukesh (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This study explores how millet-based agriculture, rooted in Uttarakhand’s traditional Barahnaja system, can diversify rural livelihoods and advance the Sustainable Development Goals (SDGs). We formulate a research question: How can the promotion of traditional millets in Uttarakhand contribute to livelihood indices and SDGs, and what is the economic impact on rural households? To address this, we review literature on millets’ roles in climate resilience, nutrition, and sustainability. We then develop a simulation model, calibrated with data from NSSO, FAO and ICAR, to compare household incomes under traditional cereal-dominated cropping versus millet-integrated farming (e.g. partial shift to finger and other small millets). The model incorporates normal and drought scenarios, reflecting Uttarakhand’s climate vulnerability. Results show that millet adoption substantially raises net income and income stability; for example, in a normal year a hectare of millet yields roughly 39,000 versus 22,000 from a traditional crop, and in drought, millet yields only slightly decline (Figure 1, Table 1). These gains stem from millets’ low input needs and drought resilience. We discuss how these findings align with SDGs – e.g. millets can reduce hunger (SDG2), improve nutrition (SDG3) and women’s livelihoods, conserve water (SDG6), and build climate resilience (SDG13). The analysis highlights that promoting millets through traditional knowledge (as in Uttarakhand’s Barahnaja) can be a sustainable pathway for economic and ecological benefits. We conclude that integrating millet cultivation into policy (e.g. MSP support, public procurement) can leverage indigenous knowledge and support multiple SDGs.